Pengaruh Komisaris Independen, Komite Audit, dan Kualitas Audit terhadap Tax Avoidance - Rusdiani, Wiwik; Umaimah, Umaimah (Journal of Culture Accounting and Auditing, 2023)
This study aims to examine whether or not there is an influence between independent commissioners, audit committees, and audit quality on tax avoidance. This research includes quantitative research using secondary data obtained from the company's annual report. The population of this study are manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the period 2018 to 2020. A total of 78 samples were selected using the purposive sampling method, and analyzed using multiple linear regression. The results showed that the independent commissioner had a significant effect on tax avoidance, while the audit committee and audit quality had no effect on tax avoidance. The results of the study imply the role of supervision and monitoring in implementing optimal corporate tax planning to reduce the level of tax avoidance.